Identifying Critical Input Parameters for Improving Drag‐Based CME Arrival Time Predictions - C. Kay; M. L. Mays; C. Verbeke (Space Weather)
Abstract Coronal mass ejections (CMEs) typically cause the strongest geomagnetic storms, so a major focus of space weather research has been predicting the arrival time of CMEs. Most arrival time models fall into two categories: (1) drag‐based models that integrate the drag force between a simplified CME structure and the background solar wind and (2) full magnetohydrodynamic models. Drag‐based models typically are much more computationally efficient than magnetohydrodynamic models, allowing for ensemble modeling. While arrival time predictions have improved since the earliest attempts, both types of models currently have difficulty achieving mean absolute errors below 10 hr. Here we use a drag‐based model ANTEATR (Another Type of Ensemble Arrival Time Results) to explore the sensitivity of arrival times to various input parameters. We consider CMEs of different strengths from average to extreme size, speed, and mass (kinetic energies between 9×1029 and 6×1032 erg). For each scale CME, we vary the input parameters to reflect the current observational uncertainty in each and determine how accurately each must be known to achieve predictions that are accurate within 5 hr. We find that different scale CMEs are the most sensitive to different parameters. The transit time of average strength CMEs depends most strongly on the CME speed, whereas an extreme strength CME is the most sensitive to the angular width. A precise CME direction is critical for impacts near the flanks but not near the CME nose. We also show that the Drag‐Based Model has similar sensitivities, suggesting that these results are representative for all drag‐based models.